Clinical benefits of a specialised clinic for hypertrophic cardiomyopathy. Issue 3 (March 2015) - Beale, A.; Macciocca, I.; Olaussen, A.; Marasco, S. F.; Mariani, J. A.; Ellims, A. H.
Abstract Background Hypertrophic cardiomyopathy (HCM) is the most common monogenic cardiac condition, with a range of investigation and management options available. Recent research has recommended management within multidisciplinary‐dedicated HCM centres. Aim To assess the clinical impact of attendance at a specialised clinic on the management of HCM. Methods A retrospective study of patients attending the HCM Clinic @ The Alfred during the first 2 years of operation was performed. Outcome measures comprised improvements in management of HCM as a result of attending the clinic including risk stratification and further investigations, medication changes, referral for implantable cardioverter‐defibrillators (ICD) and septal reduction therapy, and screening of first‐degree relatives (FDR). Results Following specialised clinic attendance, there was an increase in patients investigated with 24‐h Holter monitoring by 39%, stress echocardiography by 21% and cardiac magnetic resonance imaging by 70%. Medications were optimised in 47% of patients. Six per cent of patients underwent ICD implantation and 13% underwent septal myectomy. Seventy new FDR were screened identifying 10 new cases of HCM. Conclusions Attendance at our specialised HCM clinic leads to facilitation of cardiac investigations, optimisation of medical therapy, streamlining of referrals for ICD implantation and septal reduction therapy, and improved family screening. Referral to a specialised clinic offering comprehensive management should be considered for all patients with HCM.